A new species of Habenaria (Orchidaceae) from Nepal - Kolanowska, Marta (Phytotaxa, 2016)
With about 800 species (Govaerts et al. 2010) Habenaria Willdenow (1805: 5) is one of the largest and most widespread genera in Orchidaceae. The highest diversity of the genus occurs in Brazil, southern and central Africa and East Asia (Kurzweil & Weber 1992). Species included in Habenaria are terrestrial herbs with fleshy tubers. Their leaves are arranged variously and basally contracted into amplexicaul sheaths. The flowers are usually resupinate, with dorsal sepal forming a hood with the petals (Xinqui & Cribb 2009). The gynostemium varies significantly between the species, especially in aspects of connective and rostellum form as well as length (Szlachetko & Rutkowski 2000).